2021
DOI: 10.3389/fped.2021.728640
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Pediatric and Adult Rehabilitation Services for Young Adults With Childhood-Onset Disabilities: Evaluation of the LIFEspan Model of Transitional Care

Abstract: Background: LIFEspan (“Living Independently and Fully Engaged”) is a linked transition service model for youth and young adults with childhood-onset disabilities offered via an inter-agency partnership between two rehabilitation hospitals (one pediatric and one adult) in Toronto, Canada.Objective: The objective was to evaluate healthcare outcomes (continuity of care and healthcare utilization) for clients enrolled in LIFEspan.Methods: A prospective, longitudinal, observational mixed-method study design was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Youth who followed a mainstream pathway such as postsecondary education similarly faced challenges in navigating the ableist system. Despite mounting research and policy recommendations over the past two decades ( Kingsnorth et al, 2021 ; Lilly et al, 2019 ), the transition to adulthood still felt rough and alienating for disabled youth and families in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Youth who followed a mainstream pathway such as postsecondary education similarly faced challenges in navigating the ableist system. Despite mounting research and policy recommendations over the past two decades ( Kingsnorth et al, 2021 ; Lilly et al, 2019 ), the transition to adulthood still felt rough and alienating for disabled youth and families in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, a national guideline for transition calls for the removal of barriers to inter-agency collaboration to promote family-centred, inclusive support amenable to personal choice and health conditions ( 2 ). A small but growing body of evidence suggests that a coordinated, “warm” handover to adult service providers can increase continuity of care and health service utilization ( 7 , 8 ). Continuity of health service utilization reportedly reduced intensive re-engagement in the health system after reaching a point of crisis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has repeatedly suggested that there is a considerable gap between pediatric and adult services that hinders developmentally appropriate care provision. [1][2][3] Several researchers have indicated that suboptimal transitions can increase the risk of preventable complications and hospital admissions due to nonadherence, inadequate health management, and the loss of follow-up care by adult health providers. [4][5][6][7] With increased survival rates for persons with severe medical conditions and disabilities, the focus of transition support in pediatric services has extended from clinical services to multiple aspects of life transitions.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] With increased survival rates for persons with severe medical conditions and disabilities, the focus of transition support in pediatric services has extended from clinical services to multiple aspects of life transitions. 2,8 Following a paradigm shift toward client-and family-centered care, 9 transition to adulthood services has gradually encompassed not only clinical transfer but also additional vocational, educational, and social needs of youth with special health care needs (i.e., young clients) and their family members/caregivers. [10][11][12] A smooth, coordinated transition to adult care requires an open, ongoing collaboration among a variety of health care and social service providers, young clients, and their families.…”
Section: Introductionmentioning
confidence: 99%